Influence of Intellectual Capital, Government Support and Entrepreneurial Leadership on Organisational Performance - Eni Cahyani; Asri Riani; Mugi Harsono; Joko Suyono (Ianna Journal of Interdisciplinary Studies)
Background: There are inconsistent research results regarding the role of intellectual capital (IC), entrepreneurial leadership (EL), and government support (GS) in organisational performance (OP).